Phytochemical Analysis and Antibacterial Activity of Medicinal Plant Cardiospermum halicacabum Linn. - Sangu Murugesan2*, Maluventhan Viji1 (Journal of Phytology, 2010)
SUMMARY The crude extracts from leaf and stem of Cardiospermum halicacabum in different solvent, were subjected to pharmacognostic and fluorescence analysis, phytochemical and antimicrobial screening against selected Gram positive and Gram negative bacteria. Acetone, alcohol, benzene, chloroform and aqueous extracts of leaf and stem were used for phytochemical screening and antimicrobial activity. Phytochemical studies indicated that the leaf and stem contain a broad spectrum of secondary metabolites. Phenol, tannins and saponins were predominantly found in all the five tested solvent extracts of leaf followed by steroids, sugars, flavonoids and terpenoids (Benzene and acetone). Like wise, phenol, tannin, amino acids were predominantly found in all the tested solvent extracts of the stem. Triperpenoids were not found in any of the solvent extracts of stem. All the extracts showed varying degree of inhibitory potential against all the tested bacteria. Acetone and chloroform extracts of leaf had higher inhibitory action against Salmonella typhi and Streptococcus subtilis respectively. Acetone extracts of stem showed maximum inhibitory action against S. typhi and benzene extracts of stem had moderate inhibitory action against Escherichia coli. Key words: Cardiospermum halicacabum, Fluorescence characteristics, Pharmacognostic studies, Phytochemical screening, Antibacterial activity Maluventhan Viji and Sangu Murugesan. Phytochemical Analysis and Antibacterial Activity of Medicinal Plant Cardiospermum halicacabum Linn. . J Phytol 2/1 (2010) 68-77.